Acetic acid-resistant glass powder for front silver paste of TOPCon cell
By using a specific composition of acetic acid-resistant glass powder, the problem of insufficient acetic acid resistance performance after laser-assisted sintering technology of the front silver paste of TOPCon battery is solved, and the acetic acid attenuation rate is reduced and the electrical performance is improved, satisfying the reliability of the battery manufacturer Require.
Patent Information
- Application Number
- CN202411803364.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
After laser-assisted sintering technology, the existing TOPCon battery front silver paste has insufficient acetic acid resistance, and the acetic acid attenuation rate is higher than that of the battery manufacturer, which affects the long-term use reliability of the product.
A glass powder formed by a acetate-resistant glass powder containing a specific proportion of ZnO, SiO2, B2O3, BaO, Li2O, PbO, TiO2 and NaF was prepared by high-temperature melting and rapid cooling processes. The glass powder formed is used to prepare silver paste to improve silver Acetate resistance and electrical properties of the slurry.
The acetic acid attenuation rate is significantly reduced, reaching less than 30% required by the battery manufacturer, improving the open circuit voltage and filling factor, enhancing the formation ability of silver-silicon alloy, and improving the contact performance and reliability of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass powder for solar cell silver paste, in particular to acetic acid-resistant glass powder for TOPCon cell front silver paste. Background Art
[0002] Laser-assisted sintering technology, also known as laser-enhanced contact optimization (LECO), was patented by Cell Engineering GmbH in 2016 for recycling and repairing under-sintered PERC cells. LECO is an advanced laser sintering technology used to improve the contact between metal electrodes and silicon wafers in solar cells.
[0003] This process occurs after a fast burn-in process of screen-printed solar cells. After LECO treatment, the contact resistance of the solar cells is significantly reduced, and contacts can be formed even on low-doped emitters. The new paste for the LECO process also showed an increase in open-circuit voltage as well as a small increase in short-circuit current.
[0004] Laser assisted sintering (LECO) technology irradiates the cell with high-intensity laser and applies a deflection voltage of 10V or more, thereby generating a local current of several amperes, significantly reducing the contact resistance between metal and semiconductor, thereby improving the fill factor. LECO is suitable for all high-temperature sintering of burn-through silver paste, so it has application potential for PERC, TOPCon and BC cells.
[0005] The key to LECO is to excite more free electrons to reduce silver ions. The front of TOPCon is hole-conducting. After increasing the reverse voltage to excite a large number of free electrons, the free electrons generate instantaneous heat and high temperature (>840°C) when encountering the glass layer of nano-colloidal silver with high resistance, causing the silver paste and silicon to form a eutectic diffusion. When the resistance of the diffusion contact is reduced, the instantaneous heat disappears and the temperature decreases. The contact quality of the formed silver-silicon alloy junction is higher than that of silver crystals, which solves the front contact of the TOPCon battery and reduces the difficulty of thinning the back of the battery. Therefore, compared with PERC, LECO has a more significant effect on the conversion efficiency of TOPCon batteries. According to Cell Engineering, LECO can help TOPCon batteries increase their conversion efficiency by 0.3%-0.6%.
[0006] Currently, the TOPCon front silver paste used in the LECO process on the market has a high open circuit voltage and fill factor, but as the competition for silver paste becomes increasingly fierce, battery manufacturers are not only concerned about electrical performance efficiency but also pay more attention to the reliability of the product during long-term use. The acetic acid resistance of the battery after laser sintering is an important indicator of the reliability of the silver paste. The acetic acid attenuation rate of most LECO process TOPCon front silver pastes currently on the market is close to 70-80%, which is much higher than the 20-40% attenuation rate required by battery manufacturers. The acetic acid attenuation rate of silver paste is greatly related to the inorganic glass powder in the silver paste, so it is particularly important to develop glass powder with high efficiency and acetic acid resistance for the LECO process TOPCon front silver paste. Summary of the invention
[0007] In view of the above problems existing in the prior art, the present invention provides an acetic acid resistant glass powder for TOPCon battery front silver paste. The glass powder of the present invention can make the battery front silver paste have both acetic acid resistance and excellent electrical properties.
[0008] The technical solution of the present invention is as follows: The first object of the present invention is to provide an acetic acid-resistant glass powder for TOPCon battery front silver paste, which comprises the following raw materials in mass percentage based on the total amount of glass powder: 2.0-10.0% ZnO, 15.0-35.0% SiO2, 12.0-45.0% B2O3, 8.0-29.0% BaO, 0.1-3.5% Li2O, 5.0-50.0% PbO, 1.0-8.0% TiO2, and 0.1-2.5% NaF; the ratio of the amount of TiO2 to the sum of the amounts of TiO2 and SiO2 is 0.03-0.3; the ratio of the amount of B2O3 to the amount of PbO is 0.3-9.
[0009] In one embodiment of the present invention, the acetic acid-resistant glass powder for the front silver paste of the TOPCon battery includes the following raw materials in percentage by mass, based on the total amount of glass powder: 6.0% ZnO, 20.0% SiO2, 20.0% B2O3, 15.0% BaO, 2.0% Li2O, 30.0% PbO, 5.0% TiO2, and 2.0% NaF.
[0010] In one embodiment of the present invention, the glass transition temperature of the glass powder is 400-550°C, and the softening temperature is 600-700°C.
[0011] In one embodiment of the present invention, the glass powder has a D50 particle size of 1.0-3.5 μm and a Dmax particle size of ≤12 μm.
[0012] In one embodiment of the present invention, the glass powder has a D50 particle size of 1.2-2.0 μm and a Dmax particle size of ≤9 μm.
[0013] A second object of the present invention is to provide a method for preparing acetic acid-resistant glass powder for TOPCon battery front silver paste, the preparation method comprising the following steps: (1) Based on the total amount of glass powder, 2.0-10.0% ZnO, 15.0-35.0% SiO2, 12.0-45.0% B2O3, 8.0-29.0% BaO, 0.1-3.5% Li2O, 5.0-50.0% PbO, 1.0-8.0% TiO2 and 0.1-2.5% NaF are mixed to prepare a mixture; (2) placing the mixture in a high temperature resistant corundum crucible and heating and melting it in a muffle furnace to obtain a high temperature glass melt; (3) Pour the high-temperature molten glass into a double-roll sheet rolling machine, rapidly cool it, and roll it into glass sheets; (4) The cooled glass flakes are crushed, sieved, ground, and dried to obtain the glass powder.
[0014] In one embodiment of the present invention, in step (1), the mixing is carried out using a 5L V-type mixer, and the mixing process is specifically divided into two steps. First, the raw materials B2O3, Li2O, TiO2, and ZnO with larger specific surface areas are mixed for half an hour according to the ingredient list, and then the raw materials PbO, BaO, NaF, and SiO2 with smaller specific surface areas are added and mixed for 40 minutes to achieve the purpose of sufficient mixing.
[0015] In one embodiment of the present invention, in step (2), the heating and melting temperature is 1000-1400° C. and the time is 10-60 min.
[0016] In one embodiment of the present invention, in step (2), during heating and melting, the peak melting temperature in the muffle furnace is 1000-1200°C, and the holding time is 20-40 minutes; when the mixture is heated to 800°C, a high-temperature iron clamp is used to clamp the crucible and take it out, and a high-temperature glass plate is used to stir the molten glass. The crucible is then clamped and returned to the muffle furnace to heat to 1000-1200°C to reach the peak temperature, so that the molten glass is evenly melted without stratification.
[0017] In one embodiment of the present invention, in step (3), the twin-roll flaking mill is cooled by passing cooling water.
[0018] In one embodiment of the present invention, in step (4), a pulverizer is used to crush the glass, and the glass is passed through a 100-200 mesh screen; a planetary ball mill is used for wet fine grinding, and the finely ground glass slurry is poured into a 304 stainless steel iron plate and dried in an oven at 80°C, and then passed through a 200 mesh screen to fully screen out the hard particles that cannot be crushed, thereby obtaining the glass powder.
[0019] In one embodiment of the present invention, the grinding medium is anhydrous ethanol, the grinding tank and the balls are made of zirconium oxide, and the diameter of the zirconium oxide balls is 2 mm. The material to be ground is weighed at 200 grams, and the mass ratio of the zirconium oxide balls to the anhydrous ethanol is 2:4:1.
[0020] The glass powder of the present invention is used for preparing TOPCon battery front silver paste suitable for LECO laser enhanced contact optimization process.
[0021] In one embodiment of the present invention, the composition of the silver paste on the front side of the TOPCon battery is: 3.0wt% of the above-mentioned glass powder, 88.6wt% of silver powder, 8.0wt% of organic carrier, and 0.4wt% of organic additive.
[0022] In one embodiment of the present invention, the organic carrier is one or more of ethyl cellulose, hydroxyethyl cellulose, acrylic resin, terpineol, tributyl citrate, and butyl carbitol acetate.
[0023] In one embodiment of the present invention, the organic auxiliary agent is one or more of sodium polyamide, glyceryl monooleate, and polyoxyethylene lauryl ether.
[0024] The beneficial technical effects of the present invention are: The glass system of the present invention contains more silicon dioxide and titanium dioxide, which greatly helps the glass's resistance to acetic acid. Silicon dioxide is a glass former, and its network structure determines that it has excellent physical and chemical properties. Therefore, silicon dioxide introduced into the glass component as a glass former has better resistance to acetic acid corrosion than boron oxide and phosphorus pentoxide. An appropriate amount of silicon dioxide increases the softening temperature of the glass and also has a certain buffering effect on the glass corrosion battery surface, thereby increasing the open circuit voltage.
[0025] Although the boron oxide in the present invention is not as resistant to acetic acid as silicon dioxide, it is crucial to lowering the softening temperature of glass and improving the contact performance of N-type TOPCon cells. Since the p+ semiconductor of the cell is doped with boron, but the concentration is very low, it is not conducive to the contact with the silver paste. The introduction of boron oxide in all glass components is more conducive to the formation of silver-silicon alloy.
[0026] The glass components of the present invention specifically introduce a relatively high content of titanium dioxide, which can be used as a network intermediate with good chemical stability, and plays a key role in the resistance of glass to acetic acid corrosion. DETAILED DESCRIPTION
[0027] The present invention will be described in detail below in conjunction with the embodiments.
[0028] Example 1 An acetic acid-resistant glass powder for TOPCon battery front silver paste, the preparation method of which comprises the following steps: (1) Using a 5L V-type mixer, 45.0% B2O3, 0.5% Li2O, 2.0% TiO2 and 2.0% ZnO were mixed for half an hour, and then 5.0% PbO, 20.0% BaO, 0.5% NaF and 25.0% SiO2 were added and mixed for 40 minutes. After being fully mixed, a mixture was obtained; (2) The mixture is placed in a high-temperature resistant corundum crucible, and placed in a high-temperature muffle furnace to heat and melt at 1200°C, and the temperature is kept for 40 minutes; when the mixture is heated to 800°C, the crucible is taken out using high-temperature tongs, and the molten glass is stirred using a high-temperature glass plate. The crucible is then clamped and returned to the muffle furnace to heat to 1200°C to reach the peak temperature, so that the molten glass is melted evenly without stratification; (3) Pour the high-temperature molten glass into a double-roll sheet rolling machine with cooling water, rapidly cool it, and roll it into glass sheets; (4) The cooled glass pieces are completely crushed using a crusher, passed through a 200-mesh screen, and then poured into a zirconia ball mill and finely ground using a planetary ball mill, wherein the wet milling medium is anhydrous ethanol; the finely ground glass slurry is poured into a 304 stainless steel iron plate and dried in an oven at 80°C, and then passed through a 200-mesh screen and sealed in a can, thereby obtaining the glass powder.
[0029] The diameter of the zirconia beads is 2 mm, and the material to be ground is weighed at 200 grams, and the mass ratio of the zirconia beads to anhydrous ethanol is 2:4:1.
[0030] In this embodiment, the glass transition temperature Tg of the glass powder is 541° C., the softening temperature Tf is 700° C., the particle size D50 is 1.5 μm, and Dmax is 7.5 μm.
[0031] Example 2 An acetic acid-resistant glass powder for TOPCon battery front silver paste, the preparation method of which comprises the following steps: (1) Using a 5L V-type mixer, 30.0% B2O3, 2.0% Li2O, 1.0% TiO2 and 5.0% ZnO were mixed for half an hour, and then 28.0% PbO, 18.0% BaO, 1.0% NaF and 15.0% SiO2 were added and mixed for 40 minutes. After being fully mixed, a mixture was obtained; (2) The mixture is placed in a high-temperature resistant corundum crucible, and placed in a high-temperature muffle furnace to heat and melt at 1000°C, and the temperature is kept for 20 minutes; when the mixture is heated to 800°C, the crucible is taken out using high-temperature tongs, and the molten glass is stirred using a high-temperature glass plate, and the crucible is continued to be clamped and sent back to the muffle furnace to heat to 1000°C to reach the peak temperature, so that the molten glass is evenly melted without stratification; (3) Pour the high-temperature molten glass into a double-roll sheet rolling machine with cooling water, rapidly cool it, and roll it into glass sheets; (4) The cooled glass pieces are completely crushed using a crusher, passed through a 200-mesh screen, and then poured into a zirconia ball mill and finely ground using a planetary ball mill, wherein the wet milling medium is anhydrous ethanol; the finely ground glass slurry is poured into a 304 stainless steel iron plate and dried in an oven at 80°C, and then passed through a 200-mesh screen and sealed in a can, thereby obtaining the glass powder.
[0032] The diameter of the zirconia beads is 2 mm, and the material to be ground is weighed at 200 grams, and the mass ratio of the zirconia beads to anhydrous ethanol is 2:4:1.
[0033] In this embodiment, the glass transition temperature Tg of the glass powder is 435° C., the softening temperature Tf is 625° C., the particle size D50 is 1.3 μm, and Dmax is 7.5 μm.
[0034] Example 3 An acetic acid-resistant glass powder for TOPCon battery front silver paste, the preparation method of which comprises the following steps: (1) Using a 5L V-type mixer, 15.0% B2O3, 3.0% Li2O, 5.0% TiO2 and 2.0% ZnO were mixed for half an hour, and then 41.0% PbO, 15.0% BaO, 1.0% NaF and 18.0% SiO2 were added and mixed for 40 minutes. After being fully mixed, a mixture was obtained; (2) The mixture is placed in a high-temperature resistant corundum crucible, and placed in a high-temperature muffle furnace to heat and melt at 1200°C, and the temperature is kept for 40 minutes; when the mixture is heated to 800°C, the crucible is taken out using high-temperature tongs, and the molten glass is stirred using a high-temperature glass plate. The crucible is then clamped and returned to the muffle furnace to heat to 1200°C to reach the peak temperature, so that the molten glass is melted evenly without stratification; (3) Pour the high-temperature molten glass into a double-roll sheet rolling machine with cooling water, rapidly cool it, and roll it into glass sheets; (4) The cooled glass pieces are completely crushed using a crusher, passed through a 200-mesh screen, and then poured into a zirconia ball mill and finely ground using a planetary ball mill, wherein the wet milling medium is anhydrous ethanol; the finely ground glass slurry is poured into a 304 stainless steel iron plate and dried in an oven at 80°C, and then passed through a 200-mesh screen and sealed in a can, thereby obtaining the glass powder.
[0035] The diameter of the zirconia beads is 2 mm, and the material to be ground is weighed at 200 grams, and the mass ratio of the zirconia beads to anhydrous ethanol is 2:4:1.
[0036] In this embodiment, the glass transition temperature Tg of the glass powder is 500° C., the softening temperature Tf is 672° C., the particle size D50 is 1.6 μm, and Dmax is 7.9 μm.
[0037] Example 4 An acetic acid-resistant glass powder for TOPCon battery front silver paste, the preparation method of which comprises the following steps: (1) Using a 5L V-type mixer, 20.0% B2O3, 1.5% Li2O, 5.0% TiO2 and 3.0% ZnO were mixed for half an hour, and then 42.5% PbO, 8.0% BaO, 2.0% NaF and 18.0% SiO2 were added and mixed for 40 minutes. After being fully mixed, a mixture was obtained; (2) The mixture is placed in a high-temperature resistant corundum crucible, and placed in a high-temperature muffle furnace to heat and melt at 1100°C, and the temperature is kept for 30 minutes; when the mixture is heated to 800°C, the crucible is taken out by clamping it with high-temperature iron tongs, and the molten glass is stirred with a high-temperature glass plate. The crucible is then clamped and returned to the muffle furnace to heat to 1100°C to reach the peak temperature, so that the molten glass is melted evenly without stratification; (3) Pour the high-temperature molten glass into a double-roll sheet rolling machine with cooling water, rapidly cool it, and roll it into glass sheets; (4) The cooled glass pieces are completely crushed using a crusher, passed through a 200-mesh screen, and then poured into a zirconia ball mill and finely ground using a planetary ball mill, wherein the wet milling medium is anhydrous ethanol; the finely ground glass slurry is poured into a 304 stainless steel iron plate and dried in an oven at 80°C, and then passed through a 200-mesh screen and sealed in a can, thereby obtaining the glass powder.
[0038] The diameter of the zirconia beads is 2 mm, and the material to be ground is weighed at 200 grams, and the mass ratio of the zirconia beads to anhydrous ethanol is 2:4:1.
[0039] In this embodiment, the glass transition temperature Tg of the glass powder is 493° C., the softening temperature Tf is 665° C., the particle size D50 is 1.5 μm, and Dmax is 7.6 μm.
[0040] Example 5 An acetic acid-resistant glass powder for TOPCon battery front silver paste, the preparation method of which comprises the following steps: (1) Using a 5L V-type mixer, 20.0% B2O3, 2.0% Li2O, 5.0% TiO2 and 6.0% ZnO were mixed for half an hour, and then 30.0% PbO, 15.0% BaO, 2.0% NaF and 20.0% SiO2 were added and mixed for 40 minutes. After being fully mixed, a mixture was obtained; (2) The mixture is placed in a high-temperature resistant corundum crucible, and placed in a high-temperature muffle furnace to heat and melt at 1100°C, and the temperature is kept for 30 minutes; when the mixture is heated to 800°C, the crucible is taken out by clamping it with high-temperature iron tongs, and the molten glass is stirred with a high-temperature glass plate. The crucible is then clamped and returned to the muffle furnace to heat to 1100°C to reach the peak temperature, so that the molten glass is melted evenly without stratification; (3) Pour the high-temperature molten glass into a double-roll sheet rolling machine with cooling water, rapidly cool it, and roll it into glass sheets; (4) The cooled glass pieces are completely crushed using a crusher, passed through a 200-mesh screen, and then poured into a zirconia ball mill and finely ground using a planetary ball mill, wherein the wet milling medium is anhydrous ethanol; the finely ground glass slurry is poured into a 304 stainless steel iron plate and dried in an oven at 80°C, and then passed through a 200-mesh screen and sealed in a can, thereby obtaining the glass powder.
[0041] The diameter of the zirconia beads is 2 mm, and the material to be ground is weighed at 200 grams, and the mass ratio of the zirconia beads to anhydrous ethanol is 2:4:1.
[0042] In this embodiment, the glass transition temperature Tg of the glass powder is 481° C., the softening temperature Tf is 652° C., the particle size D50 is 1.4 μm, and Dmax is 7.4 μm.
[0043] Example 6 An acetic acid-resistant glass powder for TOPCon battery front silver paste, the preparation method of which comprises the following steps: (1) Using a 5L V-type mixer, 12.0% B2O3, 1.5% Li2O, 6.0% TiO2 and 8.0% ZnO were mixed for half an hour, and then 17.0% PbO, 25.0% BaO, 1.5% NaF and 29.0% SiO2 were added and mixed for 40 minutes. After being fully mixed, a mixture was obtained; (2) The mixture is placed in a high-temperature resistant corundum crucible, and placed in a high-temperature muffle furnace to heat and melt at 1000°C, and the temperature is kept for 20 minutes; when the mixture is heated to 800°C, the crucible is taken out using high-temperature tongs, and the molten glass is stirred using a high-temperature glass plate, and the crucible is continued to be clamped and sent back to the muffle furnace to heat to 1000°C to reach the peak temperature, so that the molten glass is evenly melted without stratification; (3) Pour the high-temperature molten glass into a double-roll sheet rolling machine with cooling water, rapidly cool it, and roll it into glass sheets; (4) The cooled glass pieces are completely crushed using a crusher, passed through a 200-mesh screen, and then poured into a zirconia ball mill and finely ground using a planetary ball mill, wherein the wet milling medium is anhydrous ethanol; the finely ground glass slurry is poured into a 304 stainless steel iron plate and dried in an oven at 80°C, and then passed through a 200-mesh screen and sealed in a can, thereby obtaining the glass powder.
[0044] The diameter of the zirconia beads is 2 mm, and the material to be ground is weighed at 200 grams, and the mass ratio of the zirconia beads to anhydrous ethanol is 2:4:1.
[0045] In this embodiment, the glass transition temperature Tg of the glass powder is 459° C., the softening temperature Tf is 636° C., the particle size D50 is 1.8 μm, and Dmax is 8.1 μm.
[0046] Example 7 An acetic acid-resistant glass powder for TOPCon battery front silver paste, the preparation method of which comprises the following steps: (1) Using a 5L V-type mixer, 18.0% B2O3, 3.0% Li2O, 7.0% TiO2 and 5.0% ZnO were mixed for half an hour, and then 11.0% PbO, 20.0% BaO, 1.0% NaF and 35.0% SiO2 were added and mixed for 40 minutes. After being fully mixed, a mixture was obtained; (2) The mixture is placed in a high-temperature resistant corundum crucible, and placed in a high-temperature muffle furnace to heat and melt at 1100°C, and the temperature is kept for 30 minutes; when the mixture is heated to 800°C, the crucible is taken out by clamping it with high-temperature iron tongs, and the molten glass is stirred with a high-temperature glass plate. The crucible is then clamped and returned to the muffle furnace to heat to 1100°C to reach the peak temperature, so that the molten glass is melted evenly without stratification; (3) Pour the high-temperature molten glass into a double-roll sheet rolling machine with cooling water, rapidly cool it, and roll it into glass sheets; (4) The cooled glass pieces are completely crushed using a crusher, passed through a 200-mesh screen, and then poured into a zirconia ball mill and finely ground using a planetary ball mill, wherein the wet milling medium is anhydrous ethanol; the finely ground glass slurry is poured into a 304 stainless steel iron plate and dried in an oven at 80°C, and then passed through a 200-mesh screen and sealed in a can, thereby obtaining the glass powder.
[0047] The diameter of the zirconia beads is 2 mm, and the material to be ground is weighed at 200 grams, and the mass ratio of the zirconia beads to anhydrous ethanol is 2:4:1.
[0048] In this embodiment, the glass transition temperature Tg of the glass powder is 486° C., the softening temperature Tf is 660° C., the particle size D50 is 1.6 μm, and Dmax is 7.8 μm.
[0049] Example 8 An acetic acid-resistant glass powder for TOPCon battery front silver paste, the preparation method of which comprises the following steps: (1) Using a 5L V-type mixer, 12.0% B2O3, 3.5% Li2O, 8.0% TiO2 and 10.0% ZnO were mixed for half an hour, and then 5.0% PbO, 29.0% BaO, 2.5% NaF and 30.0% SiO2 were added and mixed for 40 minutes. After being fully mixed, a mixture was obtained; (2) The mixture is placed in a high-temperature resistant corundum crucible, and placed in a high-temperature muffle furnace to heat and melt at 1200°C, and the temperature is kept for 40 minutes; when the mixture is heated to 800°C, the crucible is taken out using high-temperature tongs, and the molten glass is stirred using a high-temperature glass plate. The crucible is then clamped and returned to the muffle furnace to heat to 1200°C to reach the peak temperature, so that the molten glass is melted evenly without stratification; (3) Pour the high-temperature molten glass into a double-roll sheet rolling machine with cooling water, rapidly cool it, and roll it into glass sheets; (4) The cooled glass pieces are completely crushed using a crusher, passed through a 200-mesh screen, and then poured into a zirconia ball mill and finely ground using a planetary ball mill, wherein the wet milling medium is anhydrous ethanol; the finely ground glass slurry is poured into a 304 stainless steel iron plate and dried in an oven at 80°C, and then passed through a 200-mesh screen and sealed in a can, thereby obtaining the glass powder.
[0050] The diameter of the zirconia beads is 2 mm, and the material to be ground is weighed at 200 grams, and the mass ratio of the zirconia beads to anhydrous ethanol is 2:4:1.
[0051] In this embodiment, the glass transition temperature Tg of the glass powder is 537° C., the softening temperature Tf is 689° C., the particle size D50 is 1.7 μm, and Dmax is 7.8 μm.
[0052] Comparative Example 1 A glass powder for TOPCon battery front silver paste, the preparation method of which comprises the following steps: (1) Using a 5L V-type mixer, 43.0% B2O3, 0.5% Li2O and 4.0% ZnO were mixed for half an hour, and then 7.0% PbO, 23.0% BaO, 0.5% NaF and 22.0% SiO2 were added and mixed for 40 minutes. After being fully mixed, a mixture was obtained; (2) Place the mixture into a high-temperature resistant corundum crucible, heat it in a high-temperature muffle furnace at 1100°C and melt it, keeping it warm for 30 minutes; (3) Pour the high-temperature molten glass into a double-roll sheet rolling machine with cooling water, rapidly cool it, and roll it into glass sheets; (4) The cooled glass pieces are completely crushed using a crusher, passed through a 200-mesh screen, and then poured into a zirconia ball mill and finely ground using a planetary ball mill, wherein the wet milling medium is anhydrous ethanol; the finely ground glass slurry is poured into a 304 stainless steel iron plate and dried in an oven at 80°C, and then passed through a 200-mesh screen and sealed in a can, thereby obtaining the glass powder.
[0053] The diameter of the zirconia beads is 2 mm, and the material to be ground is weighed at 200 grams, and the mass ratio of the zirconia beads to anhydrous ethanol is 2:4:1.
[0054] In this embodiment, the glass transition temperature Tg of the glass powder is 562° C., the softening temperature Tf is 725° C., the particle size D50 is 1.5 μm, and Dmax is 7.4 μm.
[0055] Comparative Example 2 A glass powder for TOPCon battery front silver paste, the preparation method of which comprises the following steps: (1) Using a 5L V-type mixer, 58.0% B2O3, 0.8% Li2O, 2.0% TiO2 and 7.0% ZnO were mixed for half an hour, and then 5.0% PbO, 15.0% BaO, 0.2% NaF and 12.0% SiO2 were added and mixed for 40 minutes. After being fully mixed, a mixture was obtained; (2) Place the mixture into a high-temperature resistant corundum crucible, heat it in a high-temperature muffle furnace at 1200°C and melt it, keeping it warm for 30 minutes; (3) Pour the high-temperature molten glass into a double-roll sheet rolling machine with cooling water, rapidly cool it, and roll it into glass sheets; (4) The cooled glass pieces are completely crushed using a crusher, passed through a 200-mesh screen, and then poured into a zirconia ball mill and finely ground using a planetary ball mill, wherein the wet milling medium is anhydrous ethanol; the finely ground glass slurry is poured into a 304 stainless steel iron plate and dried in an oven at 80°C, and then passed through a 200-mesh screen and sealed in a can, thereby obtaining the glass powder.
[0056] The diameter of the zirconia beads is 2 mm, and the material to be ground is weighed at 200 grams, and the mass ratio of the zirconia beads to anhydrous ethanol is 2:4:1.
[0057] In this embodiment, the glass transition temperature Tg of the glass powder is 518° C., the softening temperature Tf is 682° C., the particle size D50 is 1.5 μm, and Dmax is 7.6 μm.
[0058] The raw material compositions and parameters of Examples 1-8 and Comparative Examples 1-2 are shown in Tables 1 and 2 below.
[0059] Table 1
[0060] Table 2
[0061] Application Examples 1-8 and Comparative Application Examples 1-2: The glass powder prepared in the above-mentioned Examples 1-8 and Comparative Examples 1-2 is prepared into silver paste, and the specific operation method is as follows: The glass powder, silver powder, organic carrier and organic additive prepared in the above-mentioned Examples 1-8 and Comparative Examples 1-2 were mixed in a certain proportion and put into a planetary mixer for uniform mixing; then the uniformly mixed premixed slurry was ground with a three-roll mill to obtain the TOPCon front silver paste. The composition of the silver paste (the mass fraction of each raw material) is shown in Table 3 below.
[0062] Table 3
[0063] Note: The components of 8% organic carrier include 1% ethyl cellulose, 2% pineol, and 5% butyl carbitol acetate; The components of 0.4% organic additives include 0.2% sodium polyamide and 0.2% monoolein. The front silver paste prepared in the application example is printed on the front of the N-type TOPCon battery cell. 20 pieces of each example paste are printed, and the maximum sintering temperature is 700-740℃. After sintering, laser assisted sintering technology (LECO) is used for treatment. The laser equipment parameter power is 15W and the bias voltage is 44V. The specifications of the battery cells after laser treatment are 182*183mm.
[0064] The method of acetic acid treatment is: take 5 cells from each group of sample slurry after laser sintering, test the IV test data first, and insert 5 cells in a special photovoltaic basket per group, then put the basket into a plastic box filled with acetic acid solution (containing 34g pure acetic acid, 300g pure water, 180g KCl), seal the lid, and keep it warm in an oven at 85℃. After 4 hours, take out the cells and conduct IV test again, so as to calculate the efficiency attenuation after acetic acid corrosion.
[0065] The electrical properties, contact resistance and cloud black edge were tested using IV tester, TLM tester and EL tester respectively. The commercially available non-acetic acid product Riyu RY01-7009T-L8 was selected as the comparative slurry (application comparative example 3). The test results before and after acetic acid treatment are shown in Tables 4 and 5 below.
[0066] Table 4
[0067] Table 5
[0068] It can be seen from the above test results that the efficiency attenuation rate of the slurry of Example 1 after acetic acid treatment with the glass powder obtained in Example 1 is high, close to 80%; the efficiency attenuation rate of the slurry of Example 2 after acetic acid treatment with the glass powder obtained in Example 2 is high, reaching about 76%; the efficiency attenuation rate of the commercially available non-acetic acid product Riyu RY01-7009T-L8 after acetic acid treatment is as high as 50% or more; the slurry of Example 1-8 using the glass powder of the present invention can achieve an efficiency attenuation rate of less than 30% after acetic acid treatment, which meets the performance requirements of the acetic acid test of the battery factory and is very helpful for the reliability of product components. Good acetic acid resistance while improving open circuit voltage and reducing contact resistance and enhancing filling factor are also crucial to the efficiency of the product. The 15.0-35.0% content of silicon dioxide in the glass component can well reduce the damage of glass to the semiconductor silicon layer and play a role in improving the open circuit voltage. Silicon dioxide is not only a glass former itself, but also a good high-temperature corrosion-resistant material. It is also very helpful to enhance acetic acid resistance in the glass system. Boron oxide can reduce the sintering temperature in the glass system, but it is easy to make the glass structure loose, which is harmful to the acid corrosion resistance. The amount of B2O3 used in the glass powder is relatively appropriate, taking into account acetic acid and efficiency. Highly active fluxing components such as lead oxide, alkaline metal lithium oxide and sodium fluoride have a great effect on the rapid opening of the silicon nitride anti-reflection film layer during the sintering process of the silver paste. Only after the silicon nitride layer is properly opened during the sintering process, the silver colloid can have a channel to quickly form a silver-silicon alloy with the silicon element in the P+ emitter under the instantaneous high temperature during the laser process, which has a good contact effect, and is very helpful in reducing the contact resistance in the IV performance and improving the FF.
[0069] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. An acetic acid resistant glass powder for TOPCon battery front silver paste, characterized in that: The glass powder comprises the following raw materials in percentage by weight based on the total amount of the glass powder: 2.0-10.0% ZnO, 15.0-35.0% SiO2, 12.0-45.0% B2O3, 8.0-29.0% BaO, 0.1-3.5% Li2O, 5.0-50.0% PbO, 1.0-8.0% TiO2, and 0.1-2.5% NaF; The ratio of TiO2 to the sum of TiO2 and SiO2 is 0.03-0.3; the ratio of B2O3 to PbO is 0.3-9.
2. The acetic acid resistant glass powder for TOPCon battery front silver paste according to claim 1, characterized in that: Calculated on the total amount of glass powder, it includes the following raw materials in percentage by mass: 6.0% ZnO, 20.0% SiO2, 20.0% B2O3, 15.0% BaO, 2.0% Li2O, 30.0% PbO, 5.0% TiO2, and 2.0% NaF.
3. The acetic acid resistant glass powder for TOPCon battery front silver paste according to claim 1, characterized in that: The glass transition temperature of glass powder is 400-550℃, and the softening temperature is 600-700℃.
4. The acetic acid resistant glass powder for TOPCon battery front silver paste according to claim 1, characterized in that: The D50 particle size of the glass powder is 1.0-3.5 μm, and the Dmax particle size is ≤12 μm.
5. A method for preparing the acetic acid resistant glass powder for the front silver paste of TOPCon battery according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Based on the total amount of glass powder, 2.0-10.0% ZnO, 15.0-35.0% SiO2, 12.0-45.0% B2O3, 8.0-29.0% BaO, 0.1-3.5% Li2O, 5.0-50.0% PbO, 1.0-8.0% TiO2 and 0.1-2.5% NaF are mixed to prepare a mixture; (2) placing the mixture in a high temperature resistant corundum crucible and heating and melting it in a muffle furnace to obtain a high temperature glass melt; (3) Pour the high-temperature molten glass into a double-roll sheet rolling machine, rapidly cool it, and roll it into glass sheets; (4) The cooled glass flakes are crushed, sieved, ground, and dried to obtain the glass powder.
6. The preparation method according to claim 5, characterized in that: In step (2), the heating and melting temperature is 1000-1400°C and the time is 10-60 minutes.
7. The preparation method according to claim 5, characterized in that: In step (3), the twin-roll flaking machine is cooled by passing cooling water.
8. The preparation method according to claim 5, characterized in that: In step (4), the glass is crushed by a pulverizer and passed through a 100-200 mesh screen; the glass is ground by a planetary ball mill using a wet fine grinding method, and the finely ground glass slurry is dried at 80° C. and then passed through a 200 mesh screen to obtain the glass powder.
9. An application of the acetic acid resistant glass powder according to claim 1, characterized in that: Used to prepare TOPCon cell front silver paste suitable for LECO laser enhanced contact optimization process.
Citation Information
Patent Citations
Photosensitive conductive paste and method for producing same
CN102033430A
Front silver-aluminum paste of high-reliability TOPCon crystalline silicon solar cell, preparation and application
CN115881338A
Method for metalizing TOPCon solar cell by using silver-coated copper paste and solar cell
CN117650184A
Glass powder for TOPCon crystalline silicon solar cell main grid slurry and preparation method thereof
CN118479742A
High-temperature-resistant and acetic-acid-resistant conductive paste and photovoltaic module
CN119069158A